2004
DOI: 10.1038/sj.cr.7290203
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-induced premature senescence with concomitant reduction of gap junctions in human fibroblasts

Abstract: To examine the role of gap junctions in cell senescence, the changes of gap junctions in cisplatin-induced premature senescence of primary cultured fibroblasts were studied and compared with the replicative senescent human fibroblasts. Dye transfer assay for gap junction function and immunofluorescent staining for connexin 43 protein distribution were done respectively. Furthermore, cytofluorimetry and DAPI fluorescence staining were performed for cell cycle and apoptosis analysis. p53 gene expression level wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 26 publications
2
21
1
Order By: Relevance
“…It was reported that platinum-based reagents, including cisplatin, affected GJIC by reducing the amount or inducing aberrant intracellular localization of connexin proteins, or by regulating the mitogen-activated protein kinase-dependent phosphorylation of specific sites on connexins (Fiorini et al, 2004;Zhao et al, 2004;Prochá zka et al, 2007). However, the effects reported here on purified, reconstituted connexin channels establish that inhibition can occur by direct interaction of cisplatin/oxaliplatin with connexin protein and that this has a detrimental effect on toxic efficacy.…”
Section: Downloaded Fromcontrasting
confidence: 48%
“…It was reported that platinum-based reagents, including cisplatin, affected GJIC by reducing the amount or inducing aberrant intracellular localization of connexin proteins, or by regulating the mitogen-activated protein kinase-dependent phosphorylation of specific sites on connexins (Fiorini et al, 2004;Zhao et al, 2004;Prochá zka et al, 2007). However, the effects reported here on purified, reconstituted connexin channels establish that inhibition can occur by direct interaction of cisplatin/oxaliplatin with connexin protein and that this has a detrimental effect on toxic efficacy.…”
Section: Downloaded Fromcontrasting
confidence: 48%
“…In isolated Hensen cells, it was shown that the ototoxic antibiotic gentamicin reduced the conductance of the gap junctions (Todt et al, 1999). In line with this observation another ototoxic drug, cisplatin, was able to uncouple the gap junctions of fibroblasts (Zhao et al, 2004). Since the effects of gentamicin on gap junction coupling of Hensen cells could be counterbalanced by application of catalase, it was concluded that gentamicin first stimulates the production of H 2 O 2 , which!…”
Section: Pharmacological Modulation Of Gap Junction Coupling In Cochlsupporting
confidence: 49%
“…Population doubling time indicates the growth rate of the placental MSCs [22], population doubling (PD) PD=ln(Nf/Ni)ln2,   where ln equals natural logarithm, Nf equals final cell count, Ni equals initial cell count Gt  =tPD, t = Time in hours after cell seeding.…”
Section: Methodsmentioning
confidence: 99%